Depressão por endogamia em híbridos simples de sorgo granífero - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The present study objective to evaluate simple hybrids of their respective generations of self - fertilization, in order to identify the effects of inbreeding depression on sorghum. The experiments were conducted at the State University of Goiás under greenhouse conditions located in the municipality of Ipameri, GO. The experimental design was a randomized block design, with 15 treatments (F1, F2 and F3), with four replications. The evaluated traits for the determination of inbreeding depression were plant height (ALT), stem diameter (DIAM), flowering (FLOR), dry shoot mass (MSPA), dry root mass (MSR), number of spikelets per plant (NEP) and grain weight per plant (PGP). The results of the analysis of variance showed significant differences (p <0.01) for all analyzed variables. All variables in F2 presented inbreeding depression with percentages for ALT, DIAM, FLOR, MSPA, MSR, NEP and PGP, with mean values of 7.9; 18.0; 4.4; 24.8; 30.7; 36.8 and 37.7%. In F3, the results showed higher average rates of inbreeding depression for ALT, FLOR, MSPA and MSR, with values of 8.7; 11.2; 29.9 and 36.9%, respectively. Hybrids 50A50, 50A70 and Buster presented estimates of inbreeding depression for most variables analyzed with variations of inbreeding rates between the F2 and F3 generations. In addition, it was concluded that the 50A50, 50A70 and Buster sorghum hybrids presented sufficient inbreeding depression to be indicated in obtaining promising lines and recurrent selection
Keywords: Sorghum bicolor; endogâmico; perda de vigor; ação gênica; melhoramento de plantas; Sorghum bicolor; endogamic; loss of vigor; gene action; plant breeding; CIENCIAS AGRARIAS